2018
DOI: 10.1016/j.mayocpiqo.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an International Remote Simulation Training Program in Critical Care Delivery: A Pilot Study

Abstract: ObjectiveTo determine the feasibility and effectiveness of a video-enabled remote simulation training program to teach a systematic, standardized approach to the evaluation and management of the critically ill patients as part of an international quality improvement intervention.Patients and MethodsIn this pilot “train-the-trainer” prospective cohort study, we provided a remote simulation-based educational program for practicing clinicians from intensive care units involved in an international quality improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 18 publications
1
45
0
Order By: Relevance
“…2. Remote simulation training [5]: When the baseline data had been collected, the center participated in remote simulation training, which included baseline training without integration of the CERTAIN tool and an advanced training session with integration of the CERTAIN tool.…”
Section: Methodsmentioning
confidence: 99%
“…2. Remote simulation training [5]: When the baseline data had been collected, the center participated in remote simulation training, which included baseline training without integration of the CERTAIN tool and an advanced training session with integration of the CERTAIN tool.…”
Section: Methodsmentioning
confidence: 99%
“…At the beginning of the COVID-19 pandemic, urban, suburban, rural, and remote centers were requesting SBE for disaster preparedness (Dubé et al, 2020a), but RRC proved particularly challenging to reach because in addition to budgetary constraints, the pandemic resulted in new public health guidelines and restricted travel (Government of Alberta, 2020). In order to facilitate COVID-19 preparedness training for RRC, existing simulation techniques were applied through a novel approach using entirely virtually-facilitated simulation (VFS) including virtual debriefing for communities with limited access to continuing medical education (Alberta Health Services eSIM Provincial Simulation Program, 2019; Cheng et al, 2020;Cheng et al, 2017;Ikeyama, Shimizu, & Ohta, 2012;Shao et al, 2017;INACSL Standards Committee, 2016). The program's rural simulationists evolved into a virtual team, leveraging their established rapport and trust with RRC clinical nurse educators for the subsequent development and implementation of VFS.…”
Section: Highlightsmentioning
confidence: 99%
“…More sophisticated options include experts completely controlling a high-fidelity simulator and running a scenario/debrief much as you would if the learners and experts were at the same facility (Figure 1 and Figure 2). The feasibility of telesimulation has been described in a number of papers [26,30,31,32] including transoceanic telesimulation [33,34]. Multiple studies have also reported that the effectiveness of remote telesimulation is at least equal to in-person training [32,35,36,37], although one study reported communication issues between participants and the facilitator [36].…”
Section: Neonatal Resuscitation Trainingmentioning
confidence: 99%